THE IMPACT OF ORGANIC FERTILIZER FROM TEMBANG FISH (Sardinella fimbriata) AND COCONUT WATER (Cocos nucifera L) ON THE GROWTH AND FRUIT OF BIRD"™S EYE CHILI PLANTS (Capsicum frutescens L.) - Azizah, Ayu Nikmatul; Maasawet, Elsje Theodora; Herliani, Herliani (Jurnal Pendidikan Matematika dan IPA, 2024)
AbstractThis research aims to determine the impact of administering varying quantities of liquid organic fertilizer obtained from tembang fish (Sardinella fimbriata) and coconut water (Cocos nucifera L) on the development and productivity of bird's eye chili plants (Capsicum frutescens L). This study was carried out in North Penajam Paser Regency from April to July 2023. This study employs a quantitative research methodology using a randomized factorial group (RAKF) design. The design has 2 factors, each with 16 treatments, and is replicated 4 times.     The measured variables consist of plant height (in centimeters), leaf count (in strands), and fresh fruit weight (in grams). The results showed that treatment P2 (25 mL POC coconut water) had a real influence on the height parameters of bird's eye chili plants. Treatment P2 showed the highest average at the age of 70 and 79 HST, namely 44 cm and 45.5 cm. Meanwhile, treatment P16 (35 mL POC of tembang fish and 75 mL POC of coconut water) results demonstrate a notable influence on the parameters of leaf number and fresh fruit weight. The P16 treatment showed the highest average number of leaves at 56, 70 and 79 HST, namely 229, 245.75 and 326 strands. Furthermore, P16 treatment produced the highest average fresh fruit weight, namely 29 grams